Why Conceptual Design Matters in Policy Formulation: A Case for an Integrated Use of Complexity Science and Engineering Design - TAEIHAGH, Araz (Institutional Knowledge at Singapore Management University, 2009)
We believe complexity science and engineering design have much to offer for addressing problems faced in policy design and formulation. Adopting tools and techniques developed in these fields can provide insights for the development of methodologies, help in avoiding common pitfalls and minimize the time required for development of solutions. The introduction of a systematic approach for exploring alternative policies using a computational methodology that utilizes integration of diverse techniques such as backcasting, conceptual design, network analysis and agent-based modelling will help in decomposing the problem into subproblems with more manageable size, and accelerate and improve the effectiveness of the process of policy-making. We present a case for policy formulation and analysis in transport sector for achieving CO2 emission targets for the UK. In particular, our ideas are based on the Hierarchical Design Method for the conceptual design of chemical processes (Douglas, 1988) and use of complexity science techniques such as network analysis and agent-based modelling. A six-step framework has been proposed and is being implemented. A library of policy measures and networks of their relations have been developed and through the analysis of these networks and the internal properties of the policy measures, using an agent-based modeling paradigm, policy alternatives are being formulated. This research constitutes the first step towards the development of a generic family of software systems to support design of policies for different sectors. The results will assist in technology transfer and have the potential to significantly improve the development of policy alternatives, accelerate the design of policies and improve their chance of success.